Effects of Mg and MgO Nanoparticles on Microstructural and Mechanical Properties of Aluminum Matrix Composite Prepared via Mechanical Alloying - Nazariyan Khozani, Behnam; Abuchenari, Aliasghar (Journal of Composites and Compounds, 2021)
Aluminum-based composites reinforced with ceramic particles have been used for many applications because of their high hardness, good wear resistance, low weight, and low thermal expansion coefficient. The Al-MgO/Mg composite was prepared in the present study. The effects of milling time and amounts of initial Mg and MgO were studied on the properties of the composite. The milled powder mixtures were subsequently analyzed by the XRD and SEM tests. Crystal sizes and internal strains were calculated using XRD data and the Williamson-Hall equation. The hardness of samples was measured by the Vickers method. The results showed that the lattice parameter significantly increased by increasing the amount of Mg. During the milling, the crystallite size, and simultaneously internal strain and hardness increased by increasing amounts of Mg and MgO. The results also showed that the effects of Mg on the composite properties were higher than MgO particles.